Trolli se ei ole poika leikki jos mie tartuttelen: frekventatiivijohdoksen kehittyminen adversatiiviseksi passiiviksi kveenissä pohjoissaamen kielikontaktin seurauksena The development of frequentative verb derivatives into adversative passive in Kven as a result of language contact with Northern Sámi - Niiranen, Leena Mirjam (AFinLA-teema, 2022)
Source at https://journal.fi/afinla/issue/view/7860 . Derivatives ending in ttele are used with a passive meaning in the Kven dialects of Porsanger and Nordreisa. This use is a result of language contact with Sami. As in the Sami model of adversative passive, these Kven passive derivatives express an unfavorable event. They are used with a subject argument which has a semantic role as a patient or experiencer and an agent expressed in the allative case. However, not many verbs have gone through this semantic change. This semantic change illustrates innovative language use among bilinguals. Both second language learners, such as those described by Siitonen (1996) but also bilinguals interpret linguistic phenomena they encounter in one language based on the knowledge of languages they already know. However, while multilinguals create innovations, only those innovations that are accepted by the entire speech community become permanent.